Disorder Of The Text Grammar Theory's Standards In Arabic: Coherence & Cohesion Terms - Ayad N. Abdullah; Zena M. Najeeb; Milood Mustafa Ashur; Elhadi Moh M Ohida (OCERINT International Organization Center of Academic Research, 2024)
Volume 2 Issue 5